Introduction of allyi and prenyl side-chains into aromatic systems by suzuki cross-coupling reactions - Gerbino, Darío César (2009)
This paper reports some studies aiming at the developement of a general protocol useful for the synthesis of allyl- and prenylaromatic compounds. The first part deals with, the preparation of boron reagents like arylboronic acids and their pinacol esters as well as of pinacol allyl- and prenylboronates. The second part of the paper is devoted to the use of these boron reagents in Suzuki-Miyaura cross-coupling reactions leading to allylation and prenylation of aromatic compounds. Of the six methods studied, the most promising re-suits were obtained by using the Pd2(dba)3-catalyzed reactions of arylboronic acids with allyl and prenyl bromides, that lead to the products of cross coupling in high yields (average 87%), and the reactions of aryl trifluoroborates with allyl and prenyl bromides catalyzed by Pd(OAc)2 that lead to the products of coupling in all cases in high yields (average 82%). © 2009 Wiley-VCH Verlag GmbH & Co. KGaA.